A sensibilidade territorial das políticas públicas: um estudo em comunidades ribeirinhas na Amazônia legal - Heidtmann Neto, Henrique Guilherme Carlos (2008)
This work is a study of the communities of Suruacá, located at the city of Santarém, and of Baixinha, located at the city of Baião, both in the state of Pará, in the eastern part of the Brazilian Amazon. The underlying research question is: to what extent the localization (territorialização) of the public policy considers the territoriality of the places upon which they act? The general goal of the research was to contribute to this discussion with the in loco analysis of the public policy process in the ribeirinho peoples in Amazon communities. This is a specific and less visible territoriality than that of other places. It is an exploratory study that aims to understand to that extent are the public policies capable of promoting actions that are adequate to the realities of the Amazon ribeirinho communities, and how this is carried on. Of the two communities studied, that of Suruacá is considered by other communities and by local stakeholders to be a model community in terms of community organization and quality of life, with a strong presence and work of the NGO Projeto Saúde e Alegria (Health and Joy Project), plus the State participation. The Baixinha community, in its turn, has a different kind of organization and does not have the direct interference of a NGO with community legitimacy, as the former. The methodology applied to the study of the two communities is part of a comparative study to observe the contrast between both and to verify how the public policies act upon the communities, seeking to account for the participation of the NGO in one and the lack of it in the other. The posture adopted in the researched territory was the notion of Participant Observation, and for the analysis of the results the Personcentered Interface Analysis was used. The study relied upon a interdisciplinary conceptual support to interpret the results of the research. The notion of public policy was used, it being the government in action, and of public action as being the public policy plus the social action. The notions of space and territoriality were drawn from Henry Lefebvre (2000) and from Milton Santos (2001), in addition to the notion of place from Peter Spink (2001). The notions of intervention, power and knowledge by Norman Long (2001) were used to compose the analytical framework of the results of the research. The results of the research suggest that a public policy can only be effective if it is able to localize and ingrain itself. Essential conditions for it are the presence of grassroots agents, internal or external to the community, their networking, and the connection and the interface that should exist among the public policies. This work aims to contribute to the debate regarding localization (territorialização) of public policies in ribeirinho communities of the Amazon, suggesting that the greater the number of grassroots agents, the better the localization and the capillarity of the public policies will be. It also contributes from the methodological viewpoint, in the sense that it suggests that the microssocial analysis can be of great value to public policy studies.